Effect of gamma irradiation on growth and corm yield of gladiolus (Gladiolus grandiflorus) varieties - CHOUDHARY, RISHIKA; KUMAR, ANUJ; KANWAR, JYOTI; KACHOULI, B K; YADAV, BALI RAM (The Indian Journal of Agricultural Sciences, 2023)
The data analysis has revealed distinct performance trends among different aspects of gladiolus cultivation. Specifically, Arka Kesar, a gladiolus variety, demonstrated superior growth characteristics, excelling in terms of plant height, the length and width of the longest leaf at both 30 and 60 days after planting (DAP). On the other hand, Arka Tilak outperformed in the number of corms and cormels per plant. Furthermore, the application of gamma irradiation at a level of 1.25 kr was found to be advantageous for several growth parameters. It positively influenced plant height, the number of leaves per hill, the length and width of the longest leaf at both 30 and 60 DAP, as well as the number of corms and cormels per plant. In conclusion, the study suggests that the Arka Kesar variety, when subjected to 1.25 kr gamma irradiation, displayed significant superiority across multiple growth parameters in gladiolus cultivation in the Malwa region of Madhya Pradesh, India. However, for corm yield specifically, Arka Tilak irradiated with 1.25 kr demonstrated better performance. These findings provide valuable insights for optimizing gladiolus cultivation practices in the region.